Pengaruh Senam Aerobik dan Motivasi Latihan Terhadap Penurunan Persentase Lemak Tubuh - muhamad sazeli rifki; Indah Putri Nuarye; Wilda Welis; Syamsuar Abbas (Program Studi Ilmu Keolahragaan - Universitas Pendidikan Indonesia, 2020)
The purpose of this study was to determine the effect of aerobic exercise and motivation on decreasing body fat percentage of members of the D'Ladies Gymnastics Gymnastics Padang. This type of research is an experiment with a factorial design By Level 2 x 2. The sample was drawn using purposive sampling technique, so that the sample amounted to 40 people with criteria aged 20-30 years. Body fat instrument using Body Fat Analyzer and training motivation using Likert scale model questionnaire. Data were analyzed using ANOVA 2 x 2 and Tukey's follow-up test at α = 0.05. The results of hypothesis testing show, (1) there is a difference in the effect of Mixed Impact aerobic exercise and Low Impact aerobic exercise on decreasing body fat percentage, (2) there is an interaction between aerobic exercise and motivation on decreasing body fat percentage, (3) there is a difference in effect. Mixed Impact aerobic exercise and Low Impact aerobic exercise seen from high training motivation, and (4) there is no difference in the effect of Mixed Impact aerobic exercise and Low Impact aerobic exercise seen from low training motivation. It can be concluded that Mixed Impact aerobic exercise is better than Low Impact aerobic exercise in reducing body fat percentage when seen from high training motivation. As for low exercise motivation, both treatments can be given to decrease the percentage of body fat